1985
DOI: 10.1111/j.1432-1033.1985.tb09107.x
|View full text |Cite
|
Sign up to set email alerts
|

Immunoquantification of epoxide hydrolase and cytochrome P‐450 isozymes in fetal and adult human liver microsomes

Abstract: Epoxide hydrolase and three cytochrome P-450 isozymes were immunochemically determined in microsomes from adult and fetal human liver and tentatively correlated with some enzyme activities. The P-450 isozymes 5, 8 and 9 present in adult liver could not be positively correlated with the total cytochrome P-450 concentration spectrophotometrically determined. In fetal liver microsomes, isozyme 8 could not be detected by either electrophoretic or immunochemical procedures. Isozyme 5 was the major isozyme present i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

6
58
0

Year Published

1991
1991
2014
2014

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 100 publications
(64 citation statements)
references
References 27 publications
(19 reference statements)
6
58
0
Order By: Relevance
“…Another crucial element is the maturity of the enzymatic system implicated in its metabolism. To date, only few data have reported the onset of P-450 isoenzymes in the human liver: these studies concluded on the presence of CYP3A protein in the fetal liver as early as the 14th week of gestation [2,[19][20][21][22][23] and the absence of proteins of the CYP2C subfamily, explaining the very low activity towards benzopyrene and mephenytoin [2, The CYP2D subfamily is a third group of P-450 genes, composed of three genes in the human species, but only one is functional 1241. We have accumulated evidence indicating that, during ontogenesis, the surge in CYP2D6 protein is mainly postnatal since its concentration rises in newborns 24 h after birth.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Another crucial element is the maturity of the enzymatic system implicated in its metabolism. To date, only few data have reported the onset of P-450 isoenzymes in the human liver: these studies concluded on the presence of CYP3A protein in the fetal liver as early as the 14th week of gestation [2,[19][20][21][22][23] and the absence of proteins of the CYP2C subfamily, explaining the very low activity towards benzopyrene and mephenytoin [2, The CYP2D subfamily is a third group of P-450 genes, composed of three genes in the human species, but only one is functional 1241. We have accumulated evidence indicating that, during ontogenesis, the surge in CYP2D6 protein is mainly postnatal since its concentration rises in newborns 24 h after birth.…”
Section: Discussionmentioning
confidence: 99%
“…Microsomes were prepared as described elsewhere [2]. Total P-450 content was determined according to Greim [13] and protein by the procedure of Lowry et al [14].…”
Section: Of Cyp2d6 Protein Contentmentioning
confidence: 99%
See 1 more Smart Citation
“…This suggests that caffeine metabolism may depend in the foetus on the major foetal liver cytochrome, CYP3A [14,[20][21][22][23]. The C-8-hydroxylation of caffeine may also be mediated by CYP3A.…”
Section: Discussionmentioning
confidence: 99%
“…Human livers were obtained within the first hour after death and microsomes were prepared as described previously [14]. No difference in the time between death and tissue freezing was noted between age groups.…”
Section: Microsomesmentioning
confidence: 99%